2018
DOI: 10.20892/j.issn.2095-3941.2018.0047
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of programmed cell death ligand 1 expression in non-Hodgkin lymphoma: a meta-analysis

Abstract: Objective:Although the prognostic value of programmed cell death-ligand 1 (PD-L1) expression in non-Hodgkin lymphoma (NHL) has been evaluated in many studies, the results remain controversial. To investigate the prognostic role of PD-L1 expression and the association between PD-L1 expression and clinicopathological features of NHL, we performed a meta-analysis.Methods:The PubMed, EMBASE, and Cochrane Library databases were searched up to November 30, 2017. The hazard ratio (HR), 95% confidence interval (CI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Many of the genes are found to play different roles through different mechanisms in different cancers. 53 56 Similarly, Siglec-15 has variable prognostic significance in diverse cancers, and even in different subtypes of the same cancer. It is well accepted that tumor heterogeneity is a major challenge in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the genes are found to play different roles through different mechanisms in different cancers. 53 56 Similarly, Siglec-15 has variable prognostic significance in diverse cancers, and even in different subtypes of the same cancer. It is well accepted that tumor heterogeneity is a major challenge in cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Oncomine results were largely consistent with the results of these analyses. Many genes play different roles in different cancers (58)(59)(60), thus explaining the variable prognostic significance of ASF1B observed among cancer types and subtypes. Such tumor heterogeneity is a significant barrier to reliable tumor treatment [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies also reported the prognostic significance of PD-L1 in various cancers. A recent meta-analysis including 2,005 patients showed that high PD-L1 expression was associated with a poor prognosis (HR = 2.04, 95% CI = 1.18–3.54, p = 0.01) in non-Hodgkin lymphoma (Zhao et al, 2018). Li’s study showed that PD-L1 overexpression could foresee worse OS and DFS in hepatocellular carcinoma (Li et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%